Effect of glycaemic control in patients with diabetes mellitus on periodontal disease severity: Efek kontrol glikemik penderita diabetes melitus terhadap keparahan penyakit periodontal - Fitriani, Juli; Oktawati, Sri (Makassar Dental Journal, 2024)
Periodontal disease is a chronic inflammation that can affect the supporting tissues of the teeth. One of the risk factors that ag-gravate periodontal disease is diabetes mellitus (DM). This article examines the effect of glycaemic control in patients with DM on the severity of periodontal disease. Literature search was conducted using various electronic databases (Pubmed, google scholar and google scholar), with the keywords glycemic control AND periodontal disease; periodontal disease AND diabetes mellitus, insulin, complication of diabetes mellitus. Literature published in the last 5 years in Indonesian and English. Several studies sug-gest that DM is a risk factor for periodontal disease and there is a reciprocal relationship between DM disease and periodontal disease severity. It was concluded that patients with uncontrolled glycaemic can aggravate periodontal disease. DM control by performing periodontal treatment can prevent the severity of periodontal disease and DM disease.